Basketball - Hareas, John. (London ; New York : DK, 2003)
Text and detailed photographs present the history, techniques, and interesting facts of basketball.
Includes index.
6.6
5-8
Keywords: Basketball -- Juvenile literature; National Basketball Association -- Juvenile literature; Basketball; National Basketball Association; Basketball; National Basketball Association